STUDENTS' CREATIVE THINKING COMPETENCIES IN WRITING DESCRIPTIVE TEXTS IN THE DESCRIPTIVE STRUCTURE OF THE SECTION - Fani Devikasari; Markhamah; Atiqa Sabardila (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Students are required to have creative thinking competencies to face challenges in the 21st century. Creative thinking is an ability that plays an important role in the 21st century because it helps students find solutions with new innovations. In Indonesian, this creative thinking competency can be used to write descriptive texts. The purpose of this study is to analyze the creative thinking competencies used by ninth-grade students of SMP Batik PK Surakarta in writing descriptive texts that focus on the structure of the description section. A qualitative approach is used in this study. The research method is a qualitative descriptive method. Document techniques and close reading techniques are the data collection techniques for this study. Content analysis techniques are chosen as the data analysis technique for this study. The results of the study show that 18.18% of students have moderate creative thinking competencies and 81.82% of students have high creative thinking competencies. From these results, it can be stated that the average ninth-grade students of SMP Batik PK Surakarta have high creative thinking competencies. The results of this study provide theoretical implications for the study of writing skills and show that there is a role of creative thinking competencies in compiling students' descriptive texts. The results of this study can be beneficial to various parties, such as teachers, students and schools. This research opens up opportunities for further research to continue the relationship between creative thinking competencies and other text writing skills.